2023
DOI: 10.1002/admt.202300727
|View full text |Cite
|
Sign up to set email alerts
|

DLP 4D Printing of Multi‐Responsive Bilayered Structures

Abstract: Advances in soft robotics strongly rely on the development and manufacturing of new responsive soft materials. In particular, light‐based 3D printing techniques, and especially, digital light processing (DLP), offer a versatile platform for the fast manufacturing of complex 3D/4D structures with a high spatial resolution. In this work, DLP all‐printed bilayered structures exhibiting reversible and multi‐responsive behavior are presented for the first time. For this purpose, liquid crystal elastomers (LCEs) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Mainik et al reported a general method for the first time to fabricate a DLP-printed multi-responsive LCE actuator based on a double-layer structure that exhibited reversible and complex actuation modes. 141 These structures are composed of an active layer made of LCE and a passivation layer made of a printable non-responsive elastomer. Multiwavelength responsiveness is easily achieved by incorporating diverse organic dyes that exhibit absorption in different regions, ranging from visible blue to the near-infrared spectral range.…”
Section: Biomimetic Soft Robotsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mainik et al reported a general method for the first time to fabricate a DLP-printed multi-responsive LCE actuator based on a double-layer structure that exhibited reversible and complex actuation modes. 141 These structures are composed of an active layer made of LCE and a passivation layer made of a printable non-responsive elastomer. Multiwavelength responsiveness is easily achieved by incorporating diverse organic dyes that exhibit absorption in different regions, ranging from visible blue to the near-infrared spectral range.…”
Section: Biomimetic Soft Robotsmentioning
confidence: 99%
“…Reproduced with permission. Copyright 2023, John Wiley & Sons, Inc. (f) Multi-wavelength responsive LCE composite actuators . Reproduced with permission.…”
Section: Applications Of 4d Printing Of Liquid Crystal Elastomersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this panorama, 4D printing represents a powerful and flexible technology to manufacture actuators with complex architectures and enhanced shape-morphing over time (the 4th dimension) after fabrication. 1,4 In particular, 4D printed bilayers are among the simplest and most investigated actuation systems, 5 where their shape transformation is generally an out-of-plane bending. Narrowing the focus to extrusion-based 4D printing, that offers several advantages over other printing techniques ( e.g.…”
Section: Introductionmentioning
confidence: 99%